Pengaruh Kinerja Lingkungan dan Biaya Lingkungan terhadap Kinerja Keuangan pada BUMN - FITRIANI, ANIS (Jurnal Ilmu Manajemen (JIM), 2013)
This research aims to examine the effect of environmental performance and environmental cost to financial performance. The sample were taken from eighteen annual reports and sustainability report of three state owned enterprises listed on the Indonesia Stock Exchange period of 2004-2011. A multiplier linear regression analysis was used to test the the effect of environmental performance and environmental cost to financial performance. This research found that environmental performance and environmental cost has effect to financial performance simultaneously. Environmental performance partially has effect positively to financial performance while environmental costs has no effecct to financial performance. Good environmental performance will be positif responded by investor that can increase stock price. Social responsibility through environmental cost incurred less attention to the needs of stakeholder so has no effect to financial performance. Keywords: environmental performance, environmental cost, and financial performance.